Impact of Reactive Sulfur Species on Entamoeba histolytica: Modulating Viability, Motility, and Biofilm Degradation Capacity - Jun Ye; Talal Salti; Eva Zanditenas; Meirav Trebicz-Geffen; Moran Benhar; Serge Ankri (Antioxidants, 2024)
Reactive sulfur species (RSS) like hydrogen sulfide (H2S) and cysteine persulfide (Cys-SSH) emerged as key signaling molecules with diverse physiological roles in the body, depending on their concentration and the cellular environment. While it is known that H2S and Cys-SSH are produced by both colonocytes and by the gut microbiota through sulfur metabolism, it remains unknown how these RSS affect amebiasis caused by Entamoeba histolytica, a parasitic protozoan that can be present in the human gastrointestinal tract. This study investigates H2S and Cys-SSH’s impact on E. histolytica physiology and explores potential therapeutic implications. Exposing trophozoites to the H2S donor, sodium sulfide (Na2S), or to Cys-SSH led to rapid cytotoxicity. A proteomic analysis of Cys-SSH-challenged trophozoites resulted in the identification of >500 S-sulfurated proteins, which are involved in diverse cellular processes. Functional assessments revealed inhibited protein synthesis, altered cytoskeletal dynamics, and reduced motility in trophozoites treated with Cys-SSH. Notably, cysteine proteases (CPs) were significantly inhibited by S-sulfuration, affecting their bacterial biofilm degradation capacity. Immunofluorescence microscopy confirmed alterations in actin dynamics, corroborating the proteomic findings. Thus, our study reveals how RSS perturbs critical cellular functions in E. histolytica, potentially influencing its pathogenicity and interactions within the gut microbiota. Understanding these molecular mechanisms offers novel insights into amebiasis pathogenesis and unveils potential therapeutic avenues targeting RSS-mediated modifications in parasitic infections.